THE DEVELOPING OF SIMPLE PROPS BASED ON GUIDED INQUIRY TO IMPROVE STUDENTS’ CRITICAL THINKING SKILL’S - Astuti Wijayanti; Desi Eka Nur Setyaningsih (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2018)
This research is aimed to 1) develop simple sciences instrument device based on a guided inquiry to improve the skill of the students on critical thinking. 2) to know the appropriateness of physic instrument based on guided inquiry.3) to know increase critical thinking skill by using the appropriateness of this instruments. This research is research and development with 4D models. The average score in an aspect based on the whole result of the assessment by media expert is 99,33%, the material expert is 88,20%, peer reviewer 83,02%, and science teacher upon the simple props is 88,41%, then it can be stated as Good (B). There is an improvement in the student’s result when doing pretest and posttest. The average score of the students when doing pretest is 5,29, and posttest is 7,9. The level of critical thinking skill of the students is on the level medium because the criteria are 0,54.